Relationship between oxidative balance indicators and Chronic Kidney Disease - Xinyun Chen; Fangyu Shi; Wenhui Yu; Chang Gao; Shenju Gou; Ping Fu (PLoS ONE, 2025)
Introduction Chronic Kidney Disease (CKD) is a growing global health issue, affecting approximately 9.1% of the world’s population. Oxidative stress is believed to play a key role in CKD development, with indicators such as the Oxidative Balance Score (OBS), Pro-Oxidant-Antioxidant Balance (PAB), and Total Antioxidant Capacity (TAC) being of particular interest. However, their association with CKD remains unclear. Methods This study conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) 2009–2018. A total of 18,951 participants were included after applying specific inclusion criteria. Logistic regression models and restricted cubic spline regression were employed to examine the associations between these oxidative balance indicators and CKD. Subgroup and interaction analyses were also conducted for further data analyses. Finally, ROC curve analysis was used to assess the predictive performance of these indicators for CKD risk. Results After adjusting for various confounding factors, higher levels of OBS and PAB were significantly associated with a reduced risk of CKD (OR = 0.97, 95% CI: 0.96–0.99, P < 0.001; OR = 0.94, 95% CI: 0.92–0.97, P < 0.001, respectively). The ORs for the highest quartiles of OBS and PAB were 0.60 (95% CI: 0.49–0.75, P < 0.001) and 0.77 (95% CI: 0.63–0.94, P = 0.013), respectively. In contrast, TAC showed no significant association with CKD. ROC curve analysis further indicated that OBS had a superior predictive ability for CKD risk (AUC = 0.579) compared to PAB (AUC = 0.519) and TAC (AUC = 0.492). Conclusion The study suggests that oxidative balance indicators, particularly OBS and PAB, are inversely associated with CKD risk, while TAC showed no significant link. OBS demonstrated the strongest predictive ability among the indicators. These findings highlight the potential role of oxidative balance in CKD prevention. Further research is needed to confirm these associations in diverse populations and to explore the underlying mechanisms.